Pelatihan Aplikasi Seed Treatment berbahan aktif Thiamethoxam dan Mefenoxam pada Benih Kedelai Edamame Kepada Petani Desa Slateng, Ledokombo, Jember - Tanzil, Ahmad Ilham; Basuki; Nurdiana Widjayanti, Fefi; Etikasari, Bety; Kartika Sari, Vega; Rahayu, Puji; Azhar Destiawan, Hisyam; Rafid Afkar, Muhammad; Avrillia Susanto, Devani; Jafri Nur Fahmy Idlain Akbar Putra, Mokhammad; Latif, Arifin (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
Jember Regency is one of the producers of edamame soybeans in East Java. Many edamame products have even been exported abroad, especially Japan. However, the obstacles in production faced by farmers are pest and disease attacks. The main pests and diseases include seed borne, soil borne and air borne. The aim of this training activity is to empower farmer groups to carry out preventive actions in cultivating edamame soybeans. The methods used are the Participatory Rural Appraisal (PRA) Model and education. The results of the service that has been carried out in increasing knowledge of science and technology related to seed treatment are that farmers' interest is very high, as evidenced by enthusiasm in participating in activities and success in producing edamame soybeans on farmers' land.